Comparative Study of Financial Performance in The Company Sampoerna TBK and Gudang Garam TBK - Muhammad Saputra, Rizky; Habiburahman (Dinasti International Journal of Management Science, 2024)
The purpose of this study was to determine the differences in financial performance between PT Sampoerna TBK and PT Gudang Garam TBK. This study compares the financial performance of PT Sampoerna TBK and PT Gudang Garam TBK using quantitative methods with comparative studies. Samples were taken purposively from the annual financial statements of the two companies in the 2020-2022 period. The variables used include current ratio, quick ratio, debt-to-asset ratio, profit margin, and return on assets. Although both companies show good financial performance, financial management should maintain and improve profitability, liquidity, and solvency. The performance evaluation of PT HM SAMPOERNA TBK indicates a decrease in liquidity and an increase in financial risk. On the other hand, PT Gudang Garam (GRM TBK) experienced fluctuations in liquidity, debt to assets ratio, profit margin, and return on assets from 2020 to 2022. Further analysis is required to understand these changes and identify corrective measures.